Body fat versus body mass index as correlates healthy aerobic fitness control body weight program among the soccer players - Zerf, Mohammed; Bengoua, Ali; Houar, Abdelatif (Book of Abstracts, 2017)
Introduction The question of ideal body weight historically is a subject of study that raises more questions than answers[1]. However, there are more accurate methods available to determine the ideal body weight. Where among health care professionals, the best-known method for assessing body size is the body mass index[2]. While weight is not the best indicator in the case of athletes due to increased bone and skeletal muscle. Since BMI is a limited perfect measure to interpret the body fat. Where It is important for the metabolic physician to know the ranges of BMI in terms of the weight category. Methods Our aims are to include the level of aerobic fitness, to evaluate the influence of body weight on aerobic fitness to control the body weight program among 160 male soccer players their age category under 19 years, tested based on cooper test as a physiological parameter to esteem VO2max, and weight-height to calculate the BMI and body fat as anthropometric measurements. Whereas our background confirms, that Body weight is easily measured, but not always the best indicator of body composition changes [3]whereabouts VO2max levelly is related to lower body Fat percent [4]. Results The most important finding of our study concerns within the correlation body fat and height as the best predictors of the VO2max level. Whereabouts the lower body fat percent is the best predictor of the adjusted aerobic fitness control body weight program among the soccer players. Discussion To esteem the adjusted body weight, we need to detect the excess body weight in the form of fat that Anita Bean, et al [5]are reported as a distinct disadvantage in …